Educação integral, políticas públicas e docência na escola pública - Araújo, Vanessa Jordão das Neves (2021)
The principles of Integral Education comprise countless documents of public policies that govern Brazilian education and contemplate the understanding of students as subjects who must have guaranteed their development in all dimensions of their learning. The research aims to analyze the conceptions of Integral Education, revealing its approximations and distances in relation to the reality of the educational units of Elementary School I and II of the São Paulo municipal education network. It is posed as a guiding question of the study in affinity with the objective: To what extent do the conceptions of Integral Education approach the proposals of full-time Education in the outskirts of the City of São Paulo? The methodology provided for in this dissertation additionally comprises the need not to restrict the research to bibliographic and documental analysis, considering the importance of expanding the methodological bases of bibliographic and documental research, considering realities experienced in one of the school units of the municipal teaching network of city of São Paulo, with regard to the object of study. Seeking to broaden the analysis and understand the Integral Education policy in the daily life of the school reality, a field research will be carried out through semi-structured interviews, with teachers involved in the implementation of the Integral Education policy in an Elementary School II as subjects. which will be presented closed and open questions contained in a previously elaborated script pertinent to the objectives related to the object of study. Through field research, the need for training and adequacy of curricular policies on Integral Education and the weaknesses in the applicability of the object of study in school practices was notable. KEYWORDS: Integral Education. Public policy. Resume